Book review: Foucault, Bourdieu e a Questão Neoliberal [Foucault, Bourdieu and the Neoliberal Question], by Christian Laval - Cláudio Zanotelli (Geografares, 2020)
Christian Laval analyzes the importance, novelty and originality of what Foucault and Bourdieu identified as neoliberalism in the late 1970s and in the 1980s. The book critically presents the contributions of two thinkers who, in different ways, have pointed out the reconfigurations and modulations of social relations, socioeconomic processes, mutations of power, but also the modes of subjectivation and forms of behavior, normative dimensions and cleavages, practices, frameworks and horizons that neoliberalism has brought. Convergences and divergences between their works are also highlighted. As common elements, a process of acceleration of the political construction of Homo oeconomicus gains relevance. The neoliberal turn and its intensification needed political leverage, normative and symbolic action. For Michel Foucault and Pierre Bourdieu, there was a need for a profound re-elaboration of the critique of the neoliberal order. In addition to the epistemological differences highlighted in the book, the prospects that result from the identification of the multiple aspects of neoliberalism and the practical propositions thought by each of them also point to different horizons: the search for sociology as a critical place against a scholastic illusion, in Bourdieu, and a possible restart from the practices and their invention, in Foucault.
Keywords: Foucault; Bourdieu; Pierre Laval; Neoliberalism